2008
DOI: 10.1093/jn/138.6.1091
|View full text |Cite
|
Sign up to set email alerts
|

Early Dietary Intervention with a Mixture of Prebiotic Oligosaccharides Reduces the Incidence of Allergic Manifestations and Infections during the First Two Years of Life

Abstract: A mixture of neutral short-chain galactooligosaccharides (scGOS) and long-chain fructooligosaccharides (lcFOS) has been shown to reduce the incidence of atopic dermatitis (AD) and infectious episodes during the first 6 mo of life. This dual protection occurred through the intervention period. The present study evaluated if these protective effects were lasting beyond the intervention period. In a prospective, randomized, double-blind, placebo-controlled design, healthy term infants with a parental history of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
393
5
23

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 470 publications
(442 citation statements)
references
References 46 publications
10
393
5
23
Order By: Relevance
“…Previous studies included infants with an increased risk for atopy, probably prone to respiratory infections. Both previous studies (17,18) showed a decrease in respiratory infections at 2 years of age indeed. The present Multicenter Infection Prevention Study population is a healthy population: all children were identified by preventive health care visits, and had a low risk for allergy.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Previous studies included infants with an increased risk for atopy, probably prone to respiratory infections. Both previous studies (17,18) showed a decrease in respiratory infections at 2 years of age indeed. The present Multicenter Infection Prevention Study population is a healthy population: all children were identified by preventive health care visits, and had a low risk for allergy.…”
Section: Discussionmentioning
confidence: 54%
“…The frequency of the suspected causes of fever and associated symptoms was more or less equally distributed as in other relevant studies (17,18,21) . However, we did not find any differences in the suspected causes of fever between the PG and CG.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A follow-up study showed that this effect persisted for a year without dietary intervention (Arslanoglu et al, 2008). The authors speculate that an immune modulating effect through the bifidogenic change in faecal microbiota composition may be responsible for this prolonged protective effect.…”
Section: Possible Role Of Inulin and Oligofructose In Alleviating Gasmentioning
confidence: 95%
“…Furthermore, clinical trials have been performed with the scGOS/lcFOS mixture in children at high risk for allergies. A reduction in the incidence of atopic dermatitis (AD) (Moro, Arslanoglu et al 2006) and the incidence of allergic manifestations during the first 6 months of life (Arslanoglu, Moro et al 2007) was observed, furthermore this reduction lasted at least until 2 years of age (Arslanoglu, Moro et al 2008).…”
Section: Nondigestible Oligosaccharidesmentioning
confidence: 99%